Fatal Pontine and Extrapontine Myelinolysis after Severe Hyponatremia Correction: A Case Report - Erika Jokubauskaitė; Patricija Skučaitė; Ieva Vienažindytė; Neringa Balčiūnienė (Neurologijos seminarai, 2024)
Pontine and extrapontine myelinolysis represents rare but serious neurological complications associated with the rapid correction of severe hyponatremia. We present a case report of a 49-year-old male who developed pontine and extrapontine myelinolysis following a rapid correction of severe hyponatremia. Initially, the patient was admitted to a district hospital on February 18, 2024 for generalized weakness and an unspecified infection, during which, his sodium level was found to be critically low at 98.6 mmol/L. Rapid treatment raised his sodium to 140 mmol/L over a short period, completing the correction within 10 days. One day after discharge, he was readmitted to the Emergency Department at the Lithuanian University of Health Sciences Hospital Kaunas Clinics on February 29, 2024, with symptoms including altered consciousness, bulbar symptoms, and limb weakness. A head Computed Tomography (CT) scan was performed in the emergency department, which ruled out cerebrovascular accidents and other structural changes in the brain. For further evaluation, the patient was admitted to the Neurology Department, where it was decided to perform a brain Magnetic Resonance Imaging (MRI) scan. As respiratory failure developed, the patient was transferred to the Neurosurgery Intensive Care Unit (NICU). The brain MRI results confirmed pontine and extrapontine myelinolysis. Based on a review of the scientific literature, treatment with methylprednisolone was initiated. The condition was complicated by septic shock with Multiple Organ Dysfunction Syndrome (MODS), with a potential infection source in the lungs. Despite the treatment provided, the patient passed away after five days in NICU. This case highlights that rapid sodium correction can lead to serious complications, such as myelinolysis. It underscores the necessity for gradual sodium correction in patients with severe hyponatremia so that to prevent irreversible neurological damage.